Case Report: Central Retinal Artery Occlusion in a COVID-19 Patient - Montesel, Andrea; Bucolo, Claudio; Mouvet, Victoria; Moret, Emmanuelle; Eandi, Chiara M. (Frontiers in Pharmacology, 2020)
We report two cases of central retinal artery occlusion (CRAO) in patients with a previous history of COVID-19 disease. This disease has been associated with inflammatory-induced homeostasis changes leading to a severe endothelial dysfunction and a procoagulant state with multi-organ involvement, but the burden of thromboembolic complications in COVID-19 patients is currently unknown. The pathogenesis of retinal artery occlusions is a multifactorial process where inflammation and hypercoagulation state are established risk factors. Even if our experience is still an anecdotal series of cases and may represent a coincidental relationship, it is likely that COVID-19 patients could be at risk of developing retinal vascular occlusions. A focused ophthalmological surveillance is advisable to prevent and manage this possible cause of severe vision loss that has an important impact in health care system.